Identification of CD101 in Glioma: A Novel Prognostic Indicator Expressed on M2 Macrophages - Liu, Yuyang; Yao, Renqi; Shi, Ying; Liu, Yuxiao; Liu, Hongyu; Liu, Jialin; Guan, Yunqian; Yao, Yongming; Chen, Ling (Frontiers in Immunology, 2022)
Glioma represents the most common primary intracranial malignancy worldwide, with low overall survival rates and limited therapeutic options. The protein CD101, mainly expressed on several immune cells, has been demonstrated to exert potent effects on blunting T cell immune responses across infectious and autoimmunity diseases. Nevertheless, the prognostic value of CD101 expression and its role in the immune microenvironment of various malignancies currently remains elusive. Herein, by adopting bioinformatics methodology, we comprehensively illustrated the potential function and predictive value of CD101 in stratifying clinical prognosis among patients with glioma, for which a high CD101 level predicted an unfavorable clinical outcome in glioma patients. Results from enrichment analyses manifested that CD101 predominantly expressed on the tumor-associated macrophages and was significantly associated with the immune regulatory processes, as evidenced by its positive correlation with immune-related genes and the putative infiltration of immune cells. Evidence provided by in-situ multicolor immunofluorescence staining further validated our findings at the protein level. Taken together, CD101 may serve as a novel biomarker in predicting clinical prognosis and immune status for glioma patients.